The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1289/ehp.94102s1205
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of remote maritime populations to coplanar PCBs.

Abstract: Two remote maritime populations were evaluated for their biological exposure to orgnochlorines in [1989][1990] Because of their high intake ofseafood, these two populations have high biological levels. One hundred nine breast milk samples from Inuit women from Arctic Quebec were analyzed to determine levels of polychlorodibenzo-p-dioxins (PCDDs), polychlorinated dibenzofrans (PCDFs), and coplanar polychlorinated bipheuWls (PCBs) including non-ortho, mono-oriho, and di-outho congeners. Total 2,3,7,-tetrachlorod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 9 publications
1
53
1
Order By: Relevance
“…In Canadian Inuit, the serum ratio of non-DL-PCBs (e.g., PCB-153) to the DL-PCB levels was higher than for Canadian Caucasians from the Arctic area (18,40). In the present study, among the 14 PCB congeners the plasma levels of 11 non-DL-PCBs and 3 mono-ortho-DL-PCBs (#105, #118, #156) were determined.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In Canadian Inuit, the serum ratio of non-DL-PCBs (e.g., PCB-153) to the DL-PCB levels was higher than for Canadian Caucasians from the Arctic area (18,40). In the present study, among the 14 PCB congeners the plasma levels of 11 non-DL-PCBs and 3 mono-ortho-DL-PCBs (#105, #118, #156) were determined.…”
Section: Discussionmentioning
confidence: 62%
“…The latter group is made up of weak AhR ligands with very low or no TEF values, whereas di-ortho PCBs are non-DL-PCBs (15). The 3 most highly bioaccumulated di-ortho PCBs (138, Plasma dioxin-like activity in Greenlandic Inuit and Danish women 153, 180) make up to 55% of the total PCBs in human matrices (16,17) and they are found in Inuit breast milk and the blood of north shore fishermen in Arctic Quebec at concentrations between 10 and 30 times higher compared with Caucasian controls, respectively (18).The higher chlorinated PCBs have the potential to inhibit the AhR function (19,20). These results emphasize that assessment of the toxicological potential of a chemical mixture is much more complex than can be deduced by a given TEQ value.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as OCPs are lipophylic and capable of being biomagnified, they could pose a serious threat to upper trophic levels of aquatic communities and potentially to humans. Many studies have reported that people consuming large amounts of contaminated seafood may have elevated concentrations of pollutants in their tissues compared with the general population (e.g., Asplund et al, 1994;Dewailly et al, 1994). From the human health viewpoint, the presence of OCPs in seafood should be of great concern due to their potential risks as they can cause a range of adverse human health effects, such as cancer, reproductive effects, and acute and chronic injury to the nervous system (Hayes et al, 1971).…”
mentioning
confidence: 99%
“…The consumption of these contaminated fish will exceed the risk-based concentration of ''zero'' recommended by the US EPA (1996). People consuming large amounts of contaminated seafood may have elevated concentration of heavy metals in their tissues compared to the general population (Asplund et al 1994;Dewailly et al 1994). A correlation between blood mercury levels and methylmercury exposure via fish consumption has been shown in several different studies (Grandjean et al 1992;Svensson et al 1992;Oskarsson et al 1996).…”
mentioning
confidence: 99%